Далекий край: Роман / С. А. Есенин ; авт. послесл., комм. Ю. Л. Прокушев - Есенин Сергей Александрович; Задорнов Николай Павлович (1978)
Экземпляры: (20190930) / Инвентарный номер: 22935 / Сис.шифр: Р2 / Авт.знак: З-15 / ББК: Р2